Population genetics - Hamilton, Matthew B. (Hoboken, NJ : Wiley-Blackwell, 2021)
'Population genetics describes the distribution of alleles in a population with regard to evolutionary processes and population structure. It is the cornerstone of modern evolutionary biology, with wide applications in fields such as conservation biology, health-oriented clinical research, bioinformatics, animal and plant breeding, and molecular biology. Population genetics can also be used as a vehicle to introduce science majors to processes of abstraction and modeling common to any field of science'--
Includes bibliographical references and index.
Keywords: Population genetics